Pre-conceptional and Peri-Gestational Maternal Binge Alcohol Drinking Produces Inheritance of Mood Disturbances and Alcohol Vulnerability in the Adolescent Offspring - Brancato, Anna; Castelli, Valentina; Cavallaro, Angela; Lavanco, Gianluca; Plescia, Fulvio; Cannizzaro, Carla (Frontiers in Psychiatry, 2018)
Although binge drinking is on the rise in women of reproductive age and during pregnancy, the consequences in the offspring, in particular the inheritance of alcohol-related mood disturbances and alcohol abuse vulnerability, are still poorly investigated. In this study, we modelled both Habitual- and Binge Alcohol Drinking (HAD and BAD) in female rats by employing a two-bottle choice paradigm, with 20% alcohol and water. The exposure started 12 weeks before pregnancy and continued during gestation and lactation. The consequences induced by the two alcohol drinking patterns in female rats were assessed before conception in terms of behavioral reactivity, anxiety- and depressive-like behavior. Afterwards, from adolescence to young-adulthood, male offspring was assessed for behavioral phenotype and alcohol abuse vulnerability. At pre-conceptional time BAD female rats showed higher mean alcohol intake and preference than HAD group; differences in drinking trajectories were attenuated during pregnancy and lactation. Pre-conceptional BAD induced a prevalent depressive/anhedonic-like behavior in female rats, rather than an increase in anxiety-like behavior, as observed in HAD rats. In the adolescent offspring, peri-gestational BAD did not affect behavioral reactivity in the open field and anxiety-like behavior in the elevated plus maze. Rather, BAD dams offspring displayed higher despair-behavior and lower social interaction with respect to control- and HAD dams progeny. Notably, only binge drinking exposure increased offspring vulnerability to alcohol abuse and relapse following forced abstinence. This is the first report showing that binge-like alcohol consumption from pre-conceptional until weaning induces relevant consequences in the affective phenotype of both the mothers and the offspring, and that such effects include heightened alcohol abuse vulnerability in the offspring. These findings highlight the need for more incisive public education campaigns about detrimental consequences of peri-gestational alcohol exposure